School Safety and Infrastructure Compliance to Requirements of Face-To-Face Classes of the Selected Public Secondary Schools - Galgo, Avelina; Curaza, Lydia Josefina (JPAIR Institutional Research, 2022)
Huge differences were expected in the new normal learning, and a significant transition was needed. While the implementation of face-to-face classes was still at the infant stage, it is very important to know the challenges of the school heads so that actions can be taken in a timely fashion. The study aimed to determine the school safety and infrastructure compliance to requirements for face-to-face classes of the selected public secondary schools in Butuan City Division. A mixed-method approach was used in the study, which was considered an appropriate approach considering the nature of the data gathered and the objectives of interest. The School Safety Assessment Tool (SSAT) was used to determine the level of readiness of schools in preparation for the safe re-opening of classes, which provided the necessary information on the improvements and adjustments to be made before the implementation of face-to-face classes. An interview guide was designed to determine the experiences and practices of school principals in relation to school management during the pandemic. Strict adherence to necessary guidelines is major preparation for schools to secure permits for the full implementation of face-to-face classes. Information drive and collaboration with stakeholders increase the sustainability aspect of face-to-face implementation. Schools have taken measures to ensure the safety of children who will be attending in-person classes, such as masks and other PPE policies for teachers, school staff, and students by national and local guidelines to enhance hygiene measures and adequate handwashing facilities, frequent cleaning of surfaces and shared objects, appropriate ventilation.